Postgraduate studies for modern languages professionals from Universidad ECCI (2015)
Learning another language has acquired more interest among people in recent years, not only because of the better job opportunities one can have, but also because it has several benefits for our health1. Those are two of the main reasons why courses related to foreign languages have become more appealing nowadays. For this project then, we have specifically taken the Modern Languages students from Universidad ECCI for a research regarding the many uncertainties that at the same time come up on them when it comes to their future, academic and work-wise, as most of them do not seem to know the Postgraduate Studies which they can pursue and / or are not fully aware about the prospective job opportunities.